1998
DOI: 10.1074/jbc.273.48.32281
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a cDNA Encoding a Novel Subtype of Rat Thyrotropin-releasing Hormone Receptor

Abstract: The thyrotropin-releasing hormone (TRH) 1 is a tripeptide (pyroglutamic acid-histidine-proline-amide) synthesized from a precursor polypeptide whose sequence contains 5 copies of the TRH sequence (5-7).Originally isolated from the hypothalamus, TRH is present in the central nervous system (thalamus, cerebral cortex, and spinal cord,) as well as in the periphery (pancreas, gastrointestinal tracts, and placenta). In the hypothalamus, TRH is synthesized by peptidergic neurons of supraoptic and paraventricular n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 29 publications
3
89
0
Order By: Relevance
“…Two G Protein-Coupled Receptor (GPCR) subtypes, designated TRHR1 and TRHR2, have been identified to date in mediating TRH actions in non-human mammalian species (Cao et al, 1998;Itadani et al, 1998;Sun et al, 2003). Recent knock-out studies in mouse indicated that TRHR2 receptors account for no more that 5% of total binding in brain and that the CNS effects of TRH and TRH analogs were lost in mice in which TRHR1 was deleted (Thirunarayanan et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Two G Protein-Coupled Receptor (GPCR) subtypes, designated TRHR1 and TRHR2, have been identified to date in mediating TRH actions in non-human mammalian species (Cao et al, 1998;Itadani et al, 1998;Sun et al, 2003). Recent knock-out studies in mouse indicated that TRHR2 receptors account for no more that 5% of total binding in brain and that the CNS effects of TRH and TRH analogs were lost in mice in which TRHR1 was deleted (Thirunarayanan et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The two TRH receptor subtypes are ϳ50% homologous, and they exhibit similar binding affinities for TRH (12)(13)(14) and activate the same signaling pathways, although TRHR2 exhibits higher basal signaling activity (14 -16). TRHR1 and 2 are expressed in distinct compartments of the brain and spinal cord (12,14,17,18), although areas have been defined where both receptor subtypes are found (12,14). This raises the question regarding the mechanism of selectivity and receptor regulation used when two individual receptors, or a putative TRHR hetero-oligomeric unit, are activated by one ligand to produce differential cellular responses.…”
Section: G-protein-coupled Receptor (Gpcr)mentioning
confidence: 99%
“…TRH is also known to have extrapituitary actions in the brain, spinal cord, cardiovascular, and gastrointestinal systems (10,11). The cloning of a second receptor for TRH (TRHR2) from rat brain and spinal cord provided a possible explanation for certain neurotransmitter actions of TRH, in particular the nociceptive and spinal cord regenerative actions (12)(13)(14). The two TRH receptor subtypes are ϳ50% homologous, and they exhibit similar binding affinities for TRH (12)(13)(14) and activate the same signaling pathways, although TRHR2 exhibits higher basal signaling activity (14 -16).…”
Section: G-protein-coupled Receptor (Gpcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…cDNAs encoding the highly conserved TRHR have been cloned from mouse, rat and hamster cell lines [8][9][10], from human brain [11] and from avian and bovine tissues [12,13]. This receptor is now also designated TRHR1, to be distinguished from TRHR2, a recently discovered subtype of the rat TRH receptor, 51 % identical to TRHR1 but with a distinct mRNA tissue distribution [14,15].…”
Section: Introductionmentioning
confidence: 99%